2023
DOI: 10.1186/s12978-023-01598-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, indications, and complications of caesarean section in health facilities across Nigeria: a systematic review and meta-analysis

Itohan Osayande,
Olakunmi Ogunyemi,
Uchenna Gwacham-Anisiobi
et al.

Abstract: Background Over 80,000 pregnant women died in Nigeria due to pregnancy-related complications in 2020. Evidence shows that if appropriately conducted, caesarean section (CS) reduces the odds of maternal death. In 2015, the World Health Organization (WHO), in a statement, proposed an optimal national prevalence of CS and recommended the use of Robson classification for classifying and determining intra-facility CS rates. We conducted this systematic review and meta-analysis to synthesise evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 81 publications
0
1
1
Order By: Relevance
“…The results of the present meta-analysis were higher than meta-analysis results from the studies conducted in 9 developing countries in South East Asia which is 13 % [ 69 ] and another two systematic review and meta-analysis from Africa: 17.6 % in Nigeria [ 70 ] and 9.9 % in Cameron [ 71 ]. However, lower than a systematic review and meta-analysis conducted in Iran found 48 % prevalence of caesarean section [ 72 ].…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The results of the present meta-analysis were higher than meta-analysis results from the studies conducted in 9 developing countries in South East Asia which is 13 % [ 69 ] and another two systematic review and meta-analysis from Africa: 17.6 % in Nigeria [ 70 ] and 9.9 % in Cameron [ 71 ]. However, lower than a systematic review and meta-analysis conducted in Iran found 48 % prevalence of caesarean section [ 72 ].…”
Section: Discussioncontrasting
confidence: 84%
“…The evidence from the reported prevalence estimate of caesarean section in developed and developing countries shows that the prevalence of caesarean section in the range of 23.5 %–63.27 % [ [24] , [25] , [26] , [27] , [28] , [29] , [30] ] and 2.1 %–29.55 % [ [31] , [32] , [33] , [34] , [35] , [36] , [37] ] respectively. Various studies undertaken in various sections of East African countries reveal varying in the prevalence of caesarean section such as: 14 % in Uganda [ 38 ], 15.6 % in Rwanda [ 39 ], 20.7 % in Zambia [ 40 ], 28.9 % in Tanzania [ 41 ] and 27.6 % in Ethiopia [ 42 ].…”
Section: Introductionmentioning
confidence: 99%